2017
DOI: 10.1371/journal.pone.0181675
|View full text |Cite
|
Sign up to set email alerts
|

Glaucomatous changes in lamina pores shape within the lamina cribrosa using wide bandwidth, femtosecond mode-locked laser OCT

Abstract: PurposeThe lamina cribrosa (LC) is known to play a critical role in the pathogenesis of glaucoma. Although it has been reported that striae-shaped or slit-shaped lamina pores are more frequent in eyes with primary open angle glaucoma (POAG), this observation is based only on fundus photography. The primary object of this study is to perform layer-by-layer comparisons of the shape of lamina pores within the LC in vivo.DesignCross-sectional study.MethodsOptic nerve head B-scans were obtained using custom-made br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…RNFL thickness (AUC=0.80 ± 0.03). This result may not be surprising as the ONH do not only exhibit neural tissue changes, but also connective tissue changes, such as bending of the peripapillary sclera [5], and changes in LC morphology and pore shape/pathway [23,24]. PointNet has the advantage of capturing some of these features while minimizing the total amount of information required to establish a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…RNFL thickness (AUC=0.80 ± 0.03). This result may not be surprising as the ONH do not only exhibit neural tissue changes, but also connective tissue changes, such as bending of the peripapillary sclera [5], and changes in LC morphology and pore shape/pathway [23,24]. PointNet has the advantage of capturing some of these features while minimizing the total amount of information required to establish a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important parts of this study was its demonstration of a method for 3D evaluation of laminar pore structure. All previously published reports have used 2D evaluation of laminar pore area with AO-SLO, [ 19 ] auto-segmentation of the laminar pores with SS-OCT [ 20 , 21 ], or have used new types of OCT. [ 22 ] However, when the disc angle is tilted, accurate evaluation of pore structure in 2D is very difficult. We found that true sphericity and the principal value (i.e., P1, 2, and 3) of the 3D structural data were significantly different in the control and glaucoma subjects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another new technology, swept-source OCT (SS-OCT), which uses a high-penetration laser to visualize and observe the deep structure of the ONH in detail, has also been used to study the LC [ 20 , 21 ]. New OCT technologies have demonstrated that in POAG eyes, the laminar pores become significantly elongated at the anterior surface of the LC, i.e., at a depth of 40 μm, but not at a depth of 80 μm [ 22 ]. This demonstrated that SS-OCT could be used to clearly show the structure of the laminar pores in living human subjects, and could improve our understanding of the details of glaucoma pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on images obtained by swept-source optical coherence tomography (OCT), Omodaka et al found that glaucoma patients had a smaller area and 3D volume of LC pores, probably due to the expanding area of connective tissue [ 13 ]. Elongation of lamina pores was more evident in primary open-angle glaucoma eyes than in normal eyes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%